Analysis of The Temporal Interaction Between Downtime and Stagnation Variables on Production Losses and Financial Performance Using The Vector Autoregression, Autoregressive Integrated Moving Average, and Vector Error Correction Model: Case Study of PT. XYZ – Lampung - Suksmanantyo Suksmanantyo; Lukmandono Lukmandono (Journal Of Social Science (JoSS), 2026)
Financial performance serves as a measure of a company's success in carrying out its operational activities. Company performance does not always follow a positive trend; there are phases where performance shows a declining trajectory, as observed at PT XYZ in Lampung. This study aims to analyze the temporal interaction of downtime and stagnation variables on production losses and the company's financial performance. This study is categorized as quantitative research, using secondary data collected through a time-series census technique for the period 2021–2025, resulting in a total of 60 observations. Data analysis was performed using the Autoregressive Integrated Moving Average (ARIMA), Vector Autoregression (VAR), and Vector Error Correction Model (VECM) methods with the aid of EViews version 12. The ARIMA forecasting results for 2026 show a constant (flat) pattern, in which all variables remain unchanged each month. Downtime is estimated to remain at 17.59 hours, stagnation at 24.90 hours, production loss at Rp1,779.88 million, and financial performance at Rp2,435.49 million throughout the year. The VAR estimation results indicate that the downtime factor does not have a significant impact on production losses and financial performance in the short term; meanwhile, the stagnation factor in the short term can affect financial performance but does not have a significant impact on production losses. The VECM estimation results indicate that neither the downtime nor the stagnation factor has a significant impact on production losses and financial performance in the short term; however, downtime can impact both production losses and financial performance over the long term.